Subject and agency in psychoanalysis : which is to be master? - Moran, Frances M. (Psychoanalytic crosscurrents., 1993)
Psychoanalysis works with words, words spoken by a subject who asks that the analyst listen. This is the belief that underlies Francis Moran's rewarding exploration of a central problem in psychoanalytic theory--namely, the separation of the concepts of subject and agency. Subject and Agency in Psychoanalysis contends that Freud simultaneously employs two frameworks for explaining agency-- one clinical and one theoretical. As a result, Freud's exploration of agency proceeds from two logically incompatible assumptions. The division between these assumptions is a part of Freud's psychoanalytic le.